To sell is human : the surprising truth about moving others - Pink, Daniel H. (Riverhead Books, 2012)
"From the bestselling author of Drive and A Whole New Mind comes an exploration of the power of selling, which each of us does every day--whether we know it or not. According to the U.S. Bureau of Labor Statistics, one in nine Americans works in sales. More than fifteen million people earn their keep by convincing someone else to make a purchase. But dig deeper and a startling truth emerges: Yes, one in nine Americans works in sales--but so do the other eight out of nine. Whether we're entrepreneurs persuading funders, employees pitching colleagues, or parents and teachers cajoling kids, we spend our days trying to move others. Today, like it or not, we're all in sales. Or as Daniel H. Pink puts it, everyone is in the "moving business." In this provocative book, Pink offers a fresh look at the art and science of selling. He shows that sales, whether pushing a product or peddling an idea, isn't what it used to be. Because of powerful economic changes, the glad-handing, truth-bending form of sales is a relic. In its place is a new approach to moving people that involves three very human qualities and four surprising skills. As he did in Drive and A Whole New Mind, Pink lays out the science for his counterintuitive insights, offers vivid examples and stories, and provides readers with tools to put the ideas into action. Smart yet accessible, bold yet well argued, this is the first book on sales for people who've never read a book about sales. It will change how you see your world and transform what you do at work, at school, and at home"--